2001
DOI: 10.1007/s11745-001-0827-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arachidonic acid distribution by conjugated linoleic acid isomers and linoleic acid in MCF‐7 and SW480 cancer cells

Abstract: The relationship between growth and alterations in arachidonic acid (AA) metabolism in human breast (MCF-7) and colon (SW480) cancer cells was studied. Four different fatty acid preparations were evaluated: a mixture of conjugated linoleic acid (CLA) isomers (c9,t11, t10,c12, c11,t13, and minor amounts of other isomers), the pure c9,t11-CLA isomer, the pure t10,c12-CLA isomer, and linoleic acid (LA) (all at a lipid concentration of 16 microg/mL). 14C-AA uptake into the monoglyceride fraction of MCF-7 cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 39 publications
12
38
0
Order By: Relevance
“…However, the data on effects of CLA on PGE 2 production seem inconsistent, as several studies have shown inhibition of PGE 2 production in vitro (Liu & Belury, 1998;Miller et al, 2001) and in CLA-supplemented rats Sugano et al, 1997Sugano et al, , 1998 and guinea pigs (Whigham et al, 2001(Whigham et al, , 2002. Other studies are in line with our current finding as they found no significant reduction of PGE 2 production in humans (Kelley et al, 2001), mice (Hayek et al, 1999) and rats (Turek et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…However, the data on effects of CLA on PGE 2 production seem inconsistent, as several studies have shown inhibition of PGE 2 production in vitro (Liu & Belury, 1998;Miller et al, 2001) and in CLA-supplemented rats Sugano et al, 1997Sugano et al, , 1998 and guinea pigs (Whigham et al, 2001(Whigham et al, , 2002. Other studies are in line with our current finding as they found no significant reduction of PGE 2 production in humans (Kelley et al, 2001), mice (Hayek et al, 1999) and rats (Turek et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…Several studies of cancer cell lines from various organs have shown a difference between t10, c12-CLA and c9, t11-CLA. Namely, the suppressive effect of CLA on COX-2 expression is affected by c9, t11-CLA, and an alternative mechanism is induced by t10, c12-CLA [44][45][46]. In our present study, supplementation with CLA-FFA and CLA-TG inhibited the expression of COX-2, PGE2, and TXB2 in the colon mucosa.…”
Section: Discussionsupporting
confidence: 56%
“…*p \ 0.05 compared with azoxymethane (AOM)-pretreated rats fed with 10% beef tallow only; **p \ 0.05 compared with saline-pretreated rats fed with 10% beef tallow only; and p \ 0.05 compared with AOM-pretreated rats in each dietary group. BT, Beef tallow alone; TG, BT and 1% conjugated linoleic acid triglyceride form; FFA, BT and 1% conjugated linoleic acid free fatty acid form J Gastroenterol (2010) 45:625-635 633 arachidonic acid distribution among cellular lipids, and an altered prostaglandin profile [46]. Several studies of cancer cell lines from various organs have shown a difference between t10, c12-CLA and c9, t11-CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase A2 preferentially detaches fatty acids from phosphatidylcholine (PC), making PC the preferential source of AA for eicosanoid synthesis. Miller et al [94] showed that CLA decreases the amount of AA stored in PC and increases it in phosphatidylethanolamine (PE) along with a subsequent decrease in the production of PGE 2. Although these researchers have reported that CLA may interfere with essential fatty acid metabolism, the more effective isomer is still controversial [92,94].…”
Section: Changes To Cell Membrane Structure and Functionmentioning
confidence: 99%